A Descriptive Analysis of Student Perceptions of Cryptocurrency as a Tool for Financial Inclusion and Government Efficiency - Khotamov Shohrukhmirzo Fattoh Ugli; Netti Siska Nurhayati; Tulaboyev Azamjon Qurbonovich (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
As digital finance has grown quickly in the Society 5.0 environment, decentralized financial instruments have become much more popular. But current cross-border systems often have operational problems that keep millions of people who don't have bank accounts from being part of global financial networks. This study seeks to ascertain university students' perceptions of cryptocurrency as a mechanism to improve financial inclusion and governmental transparency. A structured survey was administered to 40 university students employing a quantitative descriptive research design to assess their attitudes towards blockchain-based financial frameworks. The study is theoretically founded on the Technology Acceptance Model (TAM), emphasizing Perceived Usefulness. The results show that people have a very positive view of cryptocurrency's role in future financial systems (Mean: 3.72) and how quickly and clearly it can process transactions. The literature talks about theoretical risks, but the results show that students mostly think about the systemic benefits and cost-effectiveness of digital assets. This research offers policymakers significant insights into the incorporation of cryptocurrencies to lower administrative expenses and enhance economic engagement. This research enhances the literature by highlighting the socio-governmental utility of cryptocurrencies, rather than considering them merely as speculative assets.